Body Mass Index Predicts Cardiovascular Risk Factors and Inflammatory Status in Postmenopausal Women. (7th June 2021) - Singar, Saiful; Suminski, Richard; Arjmandi, Bahram; Hooshmand, Shirin; Chai, Sheau
Abstract: Objectives: Some studies have shown that hormonal changes during menopause transition may lead to weight gain. Higher body mass index (BMI) may be beneficial for bone health but not for heart health. However, these phenomena are still unclear. The present study aimed to determine whether BMI is associated with cardiovascular risk factors, and bone and inflammatory biomarkers in osteopenic postmenopausal women. Methods: In a cross-sectional study, 132 healthy osteopenic postmenopausal women (1 to 10 years) not on hormone therapy (HT) and other pharmacological agents known to affect bone were recruited. Overnight fasting blood and urine samples were collected. Multiple linear regression analyses were conducted to examine the associations between BMI and changes in CVD risk factors and inflammatory and bone biomarkers. Results: Higher BMI was significantly associated with elevated serum fasting glucose, C-reactive protein (CRP), apolipoprotein B (ApoB), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG) levels after controlling for age, years of menopause, physical activity level, and total energy intake. Based on the regression model, every one unit increase in BMI was predicted to increase fasting glucose, CRP, ApoB, TC, LDL, TG by 1.0 mg/dL, 0.1 mg/L, 1.6 mg/dL, 2.8 mg/dL, 3.2 mg/dL, and 3.3 mg/dL, respectively. BMI was not associated with bone formation and resorption biomarkers. Conclusions: BMI is a good predictor of inflammatory marker and CVD risk factors but not bone biomarkers in postmenopausal women. Future studies are needed to examine the associations of body composition (lean mass and fat mass) on CVD risk factors and bone biomarkers. Funding Sources: N/A.